The relationship between social support and posttraumatic stress symptoms among youth exposed to a natural disaster - Betty S. Lai; Melissa C. Osborne; Jennifer Piscitello; Shannon Self-Brown; Mary Lou Kelley (European Journal of Psychotraumatology, 2018)
Background: Children are a vulnerable population following a natural disaster, due to their age and dependence on adults. The primary presenting problem children report after disasters is posttraumatic stress symptoms (PTSS). Prior research suggests that PTSS is inversely related to social support, which is often disrupted after a disaster. Objective: This study examined the relationship between social support (from parents, teachers, and peers) and PTSS in children affected by Hurricane Katrina. The research contributes to the literature by examining the mechanisms that drive this relationship over time. Methods: In this study, 426 children were followed over four timepoints, beginning 3–7 months after Hurricane Katrina and concluding 25–27 months post-hurricane. Three path models analysed the relationship between social support (from parents, teachers, and peers, measured by the Social Support Scale for Children) and PTSS (measured by the UCLA PTSD Reaction Index). Covariates included child age, minority status, gender, perceived life threat, and actual life threat. Nonsignificant paths were trimmed from the final models. Global fit indices were examined to determine model fit. Results: In the parent and peer social support models, PTSS exhibited statistically significant effects on social support from one wave to the next. In the teacher model, this was only true between Waves 2 and 3. Social support showed a statistically significant effect on PTSS between Wave 2 and Wave 3 in the peer model (standardized estimate = −0.26, p < .0001). No paths from social support to PTSS were significant in the parent and teacher models. Conclusion: Findings support a social selection model in which PTSS undermine social support, particularly in the first two years post-disaster. If these findings are replicated, this suggests that, in cases of limited funding, PTSS should be prioritized, given their cascading effects on social support.